Analysis Of the Experiences of Muslim Students Who Work Part-Time in Balancing Academic, Work, and Spiritual Aspects at Muhammadiyah University of Yogyakarta - Rahima, Elsa Talitha; Tumin, Tumin (Jayapangus Press, 2025)
This study analyzes the experiences of Muslim students at Universitas Muhammadiyah Yogyakarta who work part-time in balancing academic demands, work, and spiritual aspects. Working students often face challenges in time management, fatigue, and conflicts between study and work. This study aims to understand the strategies they use in facing these challenges. This research method uses a descriptive qualitative approach, data was collected through interviews with five students who work while studying. Data collection techniques in this study were carried out through observation, interview and documentation methods. Meanwhile, data analysis techniques in this study used an interactive model starting from data collection, data reduction, data presentation, and conclusion drawing. The results showed that students developed various adjustment strategies, such as managing a more disciplined schedule, building good communication with superiors, and utilizing an Islamic-based work environment to maintain worship. In addition, Islamic values such as sincerity, tawakal, gratitude, and patience are important factors in helping them overcome the obstacles they face. This research provides insights for working students as well as educational institutions in creating policies and support that can help students balance academics, work, and spirituality.